ANALISIS TENTANG PERSEPSI MAHASISWA DALAM SISTEM PEMBELAJARAN ONLINE DI UNIVERSITAS RIAU (Studi Kasus Pandemi Wabah Covid-19) - Vannya Varadisa Viani; Ahmad Eddison; Hambali Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by problems that arise during the Covid-19 pandemic where there are no crowds or gathering of people. Initially, the conventional or face-to-face student learning system was changed to an online learning system. The formulation of the problem in this study is how the students 'perceptions of the online learning system at the University of Riau and also how the students' perceptions of the advantages and disadvantages of the online learning system at the University of Riau. The research objective was to determine students 'perceptions in the online learning system at the University of Riau and also to determine students' perceptions of the advantages and disadvantages of the online learning system at the University of Riau. The benefits of research results for students are to provide an overview of student perceptions in the online learning system at Riau University. The study population was students of the Riau University. The sample in this study was taken using a quota sampling technique. Data collection techniques are questionnaires and interviews. The data analysis technique used quantitative descriptive method. The conclusion of this study is that overall data regarding student perceptions in the online learning system at the University of Riau are in the